Communicating dataism. Issue 1 (2nd January 2023) - Adamczyk, Christopher Lee
ABSTRACT: The ideology of dataism has been highly influential during the first two decades of the 21st century, impacting emergent Big Data analytic technologies' practical application and how the public receives them. In this article, I draw upon William R. Brown's Rhetoric of Social Intervention to interpret the dataism ideology as a communication process. I argue dataism comprises constituent discourses of attention, power, and need that combine to create, reify, and maintain an understanding of Big Data technologies rooted in technoliberalism and technoutopianism. Interplay between these systems has helped keep intact a generally positive public view of Big Data, naming it a collection of innovative technologies that use large quantities of previously unused data to progress social and economic decision-making . I conclude by suggesting the ecosystem of rhetorical interventions into dataism's discourses helps explain how Big Data has grown more popular despite repeated scandals and argue interpreting dataism as a communication process offers fruitful ground for research and critical intervention.